2017
DOI: 10.1111/1365-2745.12892
|View full text |Cite
|
Sign up to set email alerts
|

Stand‐level drivers most important in determining boreal forest response to climate change

Abstract: Forest ecosystems contain several climate‐sensitive drivers that respond differentially to changes in climate and climate variability. For example, growth and regeneration processes are “stand‐scale” drivers, while natural disturbances operate at “landscape scale”. The relative contributions of these different scale drivers of change in ecosystems create great uncertainty when simulating potential responses of a forest to changes in climate. Here, we assess those contributions, along with harvesting effects, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 73 publications
(126 reference statements)
3
70
2
Order By: Relevance
“…For A. saccharum north of the 90th percentile, spring warming and recent natural disturbances interacted negatively, possibly limiting range expansion, whereas for F. grandifolia in the south, spring warming interacted positively with logging. It is possible that for some species, changes in the disturbance regime, including fire, may limit their ability to migrate and persist in the boreal forest (Boulanger, Taylor, Price, Cyr, & Sainte‐Marie, ). Using physiologically based simulations in the northeastern United States, Liang et al () reported that disturbances may expedite species' recruitment into new sites, but they had little effect on the velocity of simulated range boundary shifts.…”
Section: Discussionmentioning
confidence: 99%
“…For A. saccharum north of the 90th percentile, spring warming and recent natural disturbances interacted negatively, possibly limiting range expansion, whereas for F. grandifolia in the south, spring warming interacted positively with logging. It is possible that for some species, changes in the disturbance regime, including fire, may limit their ability to migrate and persist in the boreal forest (Boulanger, Taylor, Price, Cyr, & Sainte‐Marie, ). Using physiologically based simulations in the northeastern United States, Liang et al () reported that disturbances may expedite species' recruitment into new sites, but they had little effect on the velocity of simulated range boundary shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Giuntoli et al (2018) review hydrologic land surface models for operational flood forecasts and demonstrate high variability in the complexity of plant dynamics. It is therefore not surprising that recent projections of future riverine flooding risk have focused so heavily on shifts in atmospheric forcing with simplified or static numerical representations of vegetation (e.g., Chen et al, 2018 ;Hirabayashi et al, 2013 ;Stryker et al, 2018) despite clear evidence for climate-driven changes in the density and composition of temperate forests (Boulanger et al, 2018;Dunckel et al, 2017).…”
Section: Justification Of Ecohydrologic Model Complexitymentioning
confidence: 99%
“…The predictions achieved here are aimed to support strategic or long-term forest planning. Climate change-induced long-term changes in forest growth; however, are considered to have a more significant impact on forest conditions than both harvesting and natural disturbances [68]. We test only current forest management approaches, i.e., forest management specifications in Kupolis have been defined by best describing current forest management practices in Lithuania [41][42][43], or more precisely, as they have been during the last one to two decades.…”
Section: Incorporating Climate Change Effects In Decision Support Sysmentioning
confidence: 99%